Penerapan Bermain Sensori sebuah Studi Kasus: Anak Autisme di SLB Negeri 1 Bulukumba - Nurfadillah, Nurfadillah; Cahyani, Firdha Ardhia; Ahriani, Elmy; Paramita, Dea Ananda; Munawir, A. Nidha Eka Restuti (Jurnal Pendidikan Tambusai, 2025)
This study examines the influence of sensory play activities on the fine motor skills development and adaptive behavior of an autistic child at SLB Negeri 1 Bulukumba. Employing a qualitative case study approach, data were collected through participative observation during learning sessions, semi-structured interviews with the supervising teacher, and documentation of daily developmental progress. The participant was purposively selected based on motor skill challenges and regular sensory play involvement. Data analysis followed systematic qualitative procedures including data reduction, presentation, and conclusion drawing grounded in relevant theoretical literature. Results demonstrated notable improvements in fine motor abilities such as cutting, pasting, dough manipulation, and object transfer, reflecting enhanced hand-eye coordination and finger control. Behavioral advancements included reduced tantrums, improved focus, adherence to simple instructions, and increased independence in daily activities such as eating and dressing. Social-emotional growth was observed through emerging nonverbal communication responses like brief eye contact and gesture imitation. These findings confirm the positive role of sensory stimulation in motor development, emotional regulation, and learning readiness in children with autism. The study supports integrating sensory play within special education curricula as an effective intervention for holistic child development.